Variasi Bahasa Sosiolek dalam Film "Vina Sebelum 7 Hari" - Nur Latifatul Qalbi (LoroNG: Media Pengkajian Sosial Budaya, 2025)
Social and environmental diversity, as well as language use, can be observed not only through direct observation in society but also through works that replicate it. One such work that often portrays the realities of social life is film. “Vina Sebelum 7 Hari” is one of the films that has recently gone viral in Indonesia. This study analyzes the use of sociolect language variations in the dialogues of the film “Vina Sebelum 7 Hari.” The aim of this research is to identify and evaluate the various forms of sociolect used in the film and to understand how these language variations reflect the characters’ social status, educational level, and situational context. A qualitative method with a descriptive approach was employed in this research, using data collection techniques of non-participant observation and interactive data analysis. The findings reveal that in the dialogues of “Vina Sebelum 7 Hari,” all forms of sociolect variations are used, including acrolect, basilect, vulgar, slang, colloquial, jargon, argot, and ken. The use of these language variations not only reflects the diversity of characters and their social backgrounds but also plays an important role in creating the atmosphere and reinforcing the film’s narrative. The use of language appropriate to the context and characters helps the audience to understand the relationships among the characters and the conflicts that unfold in the film.